Impact of pH Value on Structural, Thermal, Optical and Raman Studies of Neodymium Phosphate (NdP) Nanoparticles Synthesized by Co-Precipitation Technique. Issue 205 (12th February 2020) - Verma, Seema; Raina, Bindu; Bamzai, K. K.
Abstract: The present study deals with the impact of pH value on neodymium phosphate ( NdP) nanoparticles which have been successfully synthesized via wet chemical co precipitation technique. PXRD revealed the formation of monoclinic phase, purity and crystallinity. TEM reveals spherical morphology with the formation of slight agglomeration and grain size decrease at low pH as compared to high pH. TGA/DTA suggests that as synthesized nanoparticle shows phase transition above 800 ° C. FTIR and Raman spectroscopy signifies slight shifting of bands towards lower wave number at high pH and gives relevant peaks of phosphates (PO4 3− ) group. Optical absorption with selected value of pH were studied in UV-VIS spectrophotometer and showed a strong absorbance with a tendency towards blue shift.